The Experience of Democratization in Eastern Europe
XIV, 297 p.
Keywords: Drawing on a selection of papers presented to the Fifth World Congress of Central and East European Studies held in Warsaw in August 1995, the book presents a broad cross-section of thinking about postcommunist developments in Eastern Europe and the former Soviet Union. Specialists from the region and the West apply their unique insights to challenge some conventional views on the transition. The book is both diverse and focused, suggesting that the experience of democratisation is an open-ended process in which those involved learn both from their own experience and from comparative transitions elsewhere. It provides a rich source for the comparative analysis of democratisation.